Micralymma marinum - Majka, Christopher; Klimaszewski, Jan; Lauff, Randolph (Zenodo, 2008)
Micralymma marinum (Ström, 1785) NOVA SCOTIA: Guysborough Co.: Tor Bay, 6.V.1996, R.F. Lauff, intertidal zone, (1, NSMC). This species is newly recorded in Nova Scotia and its distribution in Atlantic Canada is shown in Fig. 12. It is a widely distributed Holarctic species found in intertidal habitats throughout Europe, Russia, Iceland, Greenland, Atlantic Canada, and New England in the USA (Larsson and Gígja 1959; Thayer 1985; Böcher 1988; Campbell and Davies 1991; Downie and Arnett 1996; Herman 2001). Böcher (1988, 34) wrote, “ M. marinum is a true marine insect, presumably spending its entire life cycle in the tidal zone, where it is regularly submerged at high tide. Adults and larvae are generally found together, on vertical parts or the underside of stones and rocks …”. Adults and larvae are predaceous, feeding on Collembola such as Anurida maritima (Guérin-Méneville, 1836), mites, and Thysanura although it is possible that larvae are, at least in part, also phytophagous feeding on algae (Thayer 1985; Böcher 1988; Hammond 2000). : Published as part of Majka, Christopher, Klimaszewski, Jan & Lauff, Randolph, 2008, The coastal rove beetles (Coleoptera, Staphylinidae) of Atlantic Canada: a survey and new records, pp. 115-150 in ZooKeys 2 (2) on page 121, DOI: 10.3897/zookeys.2.2, http://zenodo.org/record/576408 : {"references": ["Larsson SG, Gigja G (1959) Coleoptera 1. Synopsis. In: Fridriksson A, Tuxen SL (Eds) The Zoology of Iceland, Volume III, Part 46 a. Ejnar Munksgaard, Copenhagen-Reykjavik, 218.", "Thayer MK (1985) Micralymma marinum (Stroem) in North America: biological notes and new distributional records (Coleoptera: Staphylinidae). Psyche 92 (1): 49 - 55.", "Bocher, J (1988) The Coleoptera of Greenland. Bioscience 26: 1 - 100.", "Campbell JM, Davies A (1991) Family Staphylinidae: rove beetles. In: Bousquet Y (Ed) Checklist of Beetles of Canada and Alaska. Agriculture Canada Research Branch, Publication 1861 / E: 86 - 124.", "Downie NM, Arnett RH, Jr (1996) The beetles of northeastern North America. Sandhill Crane Press, Gainesville, 1721 pp.", "Herman LH (2001) Catalogue of the Staphylinidae (Insecta: Coleoptera): 1758 to the end of the Second Millennium. Bulletin of the American Museum of Natural History 265: 1 - 4218.", "Hammond PM (2000) Coastal Staphylinidae (rove beetles) in the British Isles, with special reference to saltmarshes. In: Sherwood BR, Gardiner BG, Harris T (Eds) British Saltmarshes: Joint symposium on British Saltmarshes organized between the Linnean Society of London, the Royal Society for the Protection of Birds, and English Nature. Cardigan, London, 247 - 302."]}